Lycium barbarum polysaccharides protects retinal ganglion cells against oxidative stress injury - Liu, Lian; Sha, Xiao-Yuan; Wu, Yi-Ning; Chen, Meng-Ting; Zhong, Jing-Xiang (Neural regeneration research, 2020)
The accumulation of excessive reactive oxygen species can exacerbate any injury of retinal tissue because free radicals can trigger lipid peroxidation, protein damage and DNA fragmentation. Increased oxidative stress is associated with the common pathological process of many eye diseases, such as glaucoma, diabetic retinopathy and ischemic optic neuropathy. Many studies have demonstrated that Lycium barbarum polysaccharides (LBP) protects against oxidative injury in numerous cells and tissues. For the model of hypoxia we used cultured retinal ganglion cells and induced hypoxia by incubating with 200 µM cobalt chloride (CoCl2) for 24 hours. To investigate the protective effect of LBP and its mechanism of action against oxidative stress injury, the retinal tissue was pretreated with 0.5 mg/mL LBP for 24 hours. The results of flow cytometric analysis showed LBP could effectively reduce the CoCl2-induced retinal ganglion cell apoptosis, inhibited the generation of reactive oxygen species and the reduction of mitochondrial membrane potential. These findings suggested that LBP could protect retinal ganglion cells from CoCl2-induced apoptosis by reducing mitochondrial membrane potential and reactive oxygen species.